A review of pancreatic cyst fluid analysis in the differential diagnosis of pancreatic cyst lesions. (March 2014) - Boot, Christopher
Diagnosis and management of pancreatic cyst lesions is challenging as there is currently no investigation that offers both high diagnostic sensitivity and high specificity for the identification of potentially malignant lesions. Accurate classification of these lesions is vital in order to avoid unnecessary treatment of benign lesions and missed opportunities for early treatment of lesions that are malignant/pre-malignant. Pancreatic cyst fluid analysis has an important role in diagnosis, although all currently available investigations based on fluid analysis have significant limitations. Cytological analysis can reveal features that are specific for a certain class of cyst, but offers limited sensitivity in detecting malignant/pre-malignant cysts. Measurement of tumour markers, particularly carcinoembryonic antigen can also be informative. Concentrations of cyst fluid carcinoembryonic antigen tend to be higher in malignant/pre-malignant cysts, although there is a wide overlap between the various classes of cyst. A number of studies have suggested that diagnostic carcinoembryonic antigen cut-offs can be chosen that provide a high degree of specificity but limited sensitivity. Studies of the analytical validity of tumour marker assays in pancreatic cyst fluid analysis have highlighted discrepancies in some fluid specimens, which require further investigation. DNA analysis also has a role. In particular, K-Ras-2 mutational analysis appears to provide high specificity for detection of malignant/pre-malignant lesions. A number of diagnostic algorithms have been published, integrating use of available investigations in order to achieve the optimum discrimination of benign and potentially malignant cysts. Research into new biochemical markers and optimal use of available pancreatic cyst fluid analyses is ongoing.